Exercise-induced CLCF1 attenuates age-related muscle and bone decline in mice - Jae Sook Kang; Jung Ha Kim; Min Ju Kim; Byungkuk Min; Seung-Min Lee; Ga-Yeon Go; Ji-Won Kim; Seongwan Kim; Ju Yeon Kwak; Sung-Wook Chun; Wook Song; Hyo Youl Moon; et al. (Nature Communications)
Abstract Skeletal muscle undergoes many alterations with aging. However, the impact of aging on muscle’s ability to secrete myokines and its subsequent effects on the body remain largely unexplored. Here, we identify myokines that have the potential to ameliorate age-related muscle and bone decline. Notably, circulating levels of cardiotrophin-like cytokine factor 1 (CLCF1) decrease with age, while exercise significantly upregulates CLCF1 levels in both humans and rodents. Restoring CLCF1 levels in aged male mice improves their physical performance, glucose tolerance, and mitochondrial activity. Furthermore, CLCF1 protects against age-induced bone loss by inhibiting osteoclastogenesis and promoting osteoblast differentiation in aged male mice. These improvements mirror some of the effects of exercise training. Conversely, blocking CLCF1 activity significantly abolishes these beneficial effects, confirming the crucial role of CLCF1 in mediating the positive effects of exercise on muscle and bone health in male mice. These findings collectively suggest that CLCF1 may contribute to the regulation of age-associated musculoskeletal deterioration, and warrant further investigation into its potential role as a modulator of musculoskeletal health during aging.